2008
DOI: 10.1074/jbc.m802851200
|View full text |Cite
|
Sign up to set email alerts
|

ATR-dependent Activation of p38 MAP Kinase Is Responsible for Apoptotic Cell Death in Cells Depleted of Cdc7

Abstract: Cdc7 is a serine/threonine kinase that plays essential roles in the initiation of eukaryotic DNA replication and checkpoint response. In previous studies, depletion of Cdc7 by small interfering RNA was shown to induce an abortive S phase that led to the cell cycle arrest in normal human fibroblasts and apoptotic cell death in various cancer cells. Here we report that stressactivated p38 MAP kinase was activated and responsible for apoptotic cell death in Cdc7-depleted HeLa cells. The activation of p38 MAP kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…In addition, our data also indicate that the activation of p38MAPK can be mediated through both ATM and ATR. This information is extremely important, because activation of p38MAPK by g-radiation is an event that seems to be dependent on ATM (Lafarga et al, 2009), whereas in other situations such as CDC7 depletion, activation of p38MAPK appears to be dependent on ATR (Im and Lee, 2008). Our data clearly demonstrate that both proteins can be activated by 5-FU and are able to activate similar downstream signals, including p53 and p38MAPK.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, our data also indicate that the activation of p38MAPK can be mediated through both ATM and ATR. This information is extremely important, because activation of p38MAPK by g-radiation is an event that seems to be dependent on ATM (Lafarga et al, 2009), whereas in other situations such as CDC7 depletion, activation of p38MAPK appears to be dependent on ATR (Im and Lee, 2008). Our data clearly demonstrate that both proteins can be activated by 5-FU and are able to activate similar downstream signals, including p53 and p38MAPK.…”
Section: Discussionsupporting
confidence: 54%
“…First-in-class Cdc7 inhibitors have broad tumour spectrum activity in preclinical models, consistent with loss of the protective checkpoint mechanism in most tumour types. Apoptotic cancer cell death in response to Cdc7 inhibition is p53-independent and, at least in some cancer cell lines, is mediated via the stress-activated protein p38MAPK in an ATM-and Rad3-related (ATR)-dependent manner [132]. Interestingly, in addition to its function in origin firing, Cdc7 kinase has been shown to play an essential role in mediating the ATR-Chk1 pathway by phosphorylating the Chk1 activator Claspin [133,134].…”
Section: The Dna Replication Initiation Machinery-a Promising Anti-camentioning
confidence: 99%
“…Knockdown of Cdc7 has been demonstrated to cause the death of cancer cells, but not normal cells, via p53-dependent pathways which are able to arrest the cell cycle, presumably in the G 1 phase (55,56). It has also been reported that Cdc7 knockdown induced p38-dependent cell death in HeLa cells (57). Cdc7 depletion is able to induce DNA damage in cancer cells (58), and activated Chk2 is capable of stabilizing the FoxM1 transcription factor, which induces the expression of cyclin B1 (59).…”
Section: Discussionmentioning
confidence: 96%